In Memoriam.- Sir Isaiah Berlin (P. Badillo O´Farrell, pp. 483-486). Alessandro Giuliani (Ugo Leopoldo Giuliani Mallart, pp. 487-488). Antonio Verri (J.M.S., p. 489). - -, - (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 9-10 (1998). 498 págs. ISBN 1130-7498